Perilaku Pengelolaan Sampah Pada Ibu Rumah Tangga Di Kelurahan Patokan Kabupaten Situbondo - Puspitasari, Silviana Ayu; Subhi, Misbahul; Saktiawan, Yusup (POLTEKKES KEMENKES MANADO, 2022)
Waste is a national problem which the management system needs to be carried out in a comprehensive and integrated manner in order to provide economic benefits, healthy for the community and safe for the environment. The type of waste that needs to be managed properly and correctly is household waste. One of the factors that influence the success of household waste management is the knowledge, attitude and good behavior of housewives. This study aims to determine the effect of knowledge and attitudes on waste management behavior among housewives in Patokan Village, Situbondo Regency. This study used an analytic observational research design with a cross sectional design. The research sample amounted to 30 people criteria using total sampling technique. The instruments used are questionnaires and observation sheets. Analysis of research results using ordinal logistic regression test. Based on the results of the ordinal logistic regression test, it was found that the significant value was 0.195. So, it can be concluded that there is no effect of knowledge and attitudes on waste management behavior in housewives in Patokan Village, Situbondo Regency. It is expected that housewives provide trash bins that meet the requirements and maintain environmental cleanliness by not burning garbage.